2022
DOI: 10.22541/au.164470075.56901729/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Copy number variants and placental abnormalities in stillborn fetuses: a secondary analysis of the Stillbirth Collaborative Research Network study

Abstract: Objective To examine the association of DNA copy number variants (CNVs) with pathologic placental lesions (PPLs) in stillborn fetuses. Design A secondary analysis of stillbirth cases in the Stillbirth Collaborative Research Network case-control study. Setting Multicenter, 59 hospitals in 5 geographic regions in the USA. Population 387 stillbirth cases (2006-2008). Methods Using standard definitions, PPLs were categorized by type including maternal and fetal vascular, inflammatory and immune/idiopathic lesions.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 35 publications
1
6
0
Order By: Relevance
“…Among 384 stillbirth cases, 58 (15.1%) had abnormal CNVs and 326 (84.9%) had normal CNVs. As previously described, 10 cases with abnormal CNVs were older, Hispanic, and with any fetal structural malformations in comparison to cases with normal CNVs. Similarly, cases with abnormal CNVs were not different in their proportions from those with normal CNVs in regard to other socio-economic factors, parity, fetal sex, maternal chronic hypertension, preeclampsia, diabetes and gestational diabetes.…”
Section: Resultssupporting
confidence: 65%
See 1 more Smart Citation
“…Among 384 stillbirth cases, 58 (15.1%) had abnormal CNVs and 326 (84.9%) had normal CNVs. As previously described, 10 cases with abnormal CNVs were older, Hispanic, and with any fetal structural malformations in comparison to cases with normal CNVs. Similarly, cases with abnormal CNVs were not different in their proportions from those with normal CNVs in regard to other socio-economic factors, parity, fetal sex, maternal chronic hypertension, preeclampsia, diabetes and gestational diabetes.…”
Section: Resultssupporting
confidence: 65%
“…8 Interpreting the pathogenicity of CNVs, however, remains challenging, 6 as limited studies link relevant clinical information to genetic observations in a structured way. Following our recent work on CNVs and placental abnormalities, 10 we used our multicenter setting of stillbirth population to determine specific CNVs associated with fetal structural malformations. We hypothesized that duplicated or deleted pathogenic CNVs in fetal/placental genes are associated with fetal structural malformations.…”
Section: Introductionmentioning
confidence: 99%
“…Their study likely captured many fetal death cases (16-23 weeks) which share pathophysiological characteristics of fetal death at ≥20 weeks. 17 Indeed, the median (IQR) gestational age in weeks among women with high-risk stillbirth FSIR was lower (29 [23][24][25][26]) than that in all affected women (39 [38][39][40]) included in our study.…”
Section: F I G U R E 2 Stillbirth Odds Among Relatives Of Parents Aff...mentioning
confidence: 59%
“…There are many pathophysiologic mechanisms by which genetic abnormalities may lead to stillbirth. Genetic changes resulting in placental insufficiency, severe fetal growth restriction, anatomic anomalies 37,38 not readily identified by ultrasound and metabolic derangements have been proposed as causative or contributory. 39 Stanley et al 4 performed whole exome sequencing in a large stillbirth case cohort and identified previously unknown genetic variants leading to a suspected genetic cause of death in 18% of the stillbirths in the study cohort.…”
Section: F I G U R E 2 Stillbirth Odds Among Relatives Of Parents Aff...mentioning
confidence: 99%
See 1 more Smart Citation